Evaluating sequential application of pre and post emergence herbicides in direct- seeded rice - Dhaker, Devi Lal; Kumar, Birendra; Karthik, Rayapati; Raj, Manish (ORYZA-An International Journal of Rice, 2023)
A field experiment was conducted at Agriculture Research Farm, Bihar Agricultural University, Sabour, Bhagalpur, Bihar during kharif season of 2018-19 to study the effect of different herbicides on weed species, growth attributes and yields of direct seeded rice. The experiment comprised of 11 treatments based on weed management practices. The 11 treatments were lone application of pendimethalin and pyrazosulfuron as pre-emergence herbicides while others were as post-emergence at 20 days after sowing i.e. pyrazosulfuron @ 25 g/ha PE, pendimethalin @1000 g/ha PE, pyrazosulfuron @ 25 g /ha PE fb 2,4-DEE @ 750 g/ha POE, pyrazosulfuron @ 25 g /ha PE fb bispyriba-Na @ 25 g/ha POE, pyrazosulfuron @ 25 g/ha PE fb bispyribac-Na @ 20 g/ha + pyrazosulfuron @ 20 g/ha POE, bispyribac-Na @ 25 g/ha POE, bispyribac-Na @ 20 g/ha + pyrazosulfuron @ 20 g/ha POE, ethoxysulfuron @ 15 g/ha + pyrazosulfuron @ 20 g /ha POE, halosulfuron @ 67.5 g/ha + azimsulfuron @ 30 g/ha POE, hand weeding thrice and weed check. Among all the herbicidal treatments, the minimum weed density (5.13 m-2), dry weight (4.82 g m-2), highest grain yield (5.41 t/ha) and benefit cost ratio (1.9) were recorded with application of pyrazosulfuron @ 25 g/ha PE fb bispyribac-Na @ 20 g/ha + pyrazosulfuron @ 20 g/ha POE.